MEDIACRACY IN THE POLITICAL SYSTEM OF MANAGEMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the concept of mediaocracy and its role in modern politicalprocesses. The authors analyze how media organizations and media interests can influence theformation of public opinion, political decisions and elections through the mechanisms of mediaattention, opinion formation, information control and funding. The article also discusses potentialchallenges and risks associated with mediacracy and possible measures to ensure balance andtransparency in political communication in the information society.
Keywords: mediocracy, electoral technologies, elections, election campaign, political party, candidate, electorate, political marketing, communication, mass-media.